The true loves knot untied Being the right path, whereby to advise princely virgins how to behave themselves, by the example of the renowned princess, the Lady Arabella, and the second son to the Lord Seymore, Late Earl of Hertford. The the tune of, Frogs Galliards (Early English Books Online / EEBO, 1630)
eebo-0166